Elevating sugar beet by-products into healthier, natural, and functional ingredients - Ahmet Görgülü (Exploration of Foods and Foodomics, 2025)
Aim: This research was conducted on the hypothesis that refined sugars negatively affect health, require high energy for production, generate significant carbon emissions, and produce environmental waste. Additionally, by-products such as molasses and pulp, which are often underutilized, can be repurposed as value-added products for human consumption. This research focuses on a new, long-shelf-life product derived from sugar beet. The developed product retains nutrients such as protein, fiber, vitamins, and minerals that are naturally present in sugar beet. Methods: The new method proposes using the entire beet as an unrefined alternative to refined sugar. The processing steps include cleaning, cooking, peeling, shredding, drying, and grinding. Various cooking methods were tested, and the optimum conditions were found to be 4.5 hours at 165°C. To prevent oxidation of peeled beets, a 0.5% citric acid solution was applied for 15 min at 25°C prior to cooking. Drying was performed in a convection oven with pans at 95°C for 7.5 hours. Results: The final product had a moisture content of 2.9% and a water activity level of 0.302. The product contained 78.6% total sugars, 12.9% fiber, and 3.45% protein, and was classified as an unrefined sweetener rich in both protein and fiber. Compared to the typical yield of 120 g of refined sugar from 1 kg of beets, this new method produces 219 g of product by utilizing fibers, proteins, and other nutrients, along with by-products such as molasses and pulp. Conclusions: Due to its high fiber and protein content, the new product has a low glycemic index. Compared to conventional beet sugar production, the proposed method reduces energy consumption and carbon emissions by 40% per unit of product. The new input obtained has a high potential to be used as a source of sugar and fiber in bakery and confectionery products. It is a more sustainable process than refined sugar.